2016
DOI: 10.1037/bul0000030
|View full text |Cite
|
Sign up to set email alerts
|

From primed concepts to action: A meta-analysis of the behavioral effects of incidentally presented words.

Abstract: A meta-analysis assessed the behavioral impact of and psychological processes associated with presenting words connected to an action or a goal representation. The average and distribution of 352 effect sizes (analyzed using fixed-effects and random-effects models) was obtained from 133 studies (84 reports) in which word primes were incidentally presented to participants, with a non-opposite control group, prior to measuring a behavioral dependent variable. Findings revealed a small behavioral priming effect (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
230
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(250 citation statements)
references
References 203 publications
(501 reference statements)
19
230
0
1
Order By: Relevance
“…If no meaningful goal exists for the person in the current situation, then the broad ensemble of situational cues is unlikely to activate relevant situated conceptualizations, which most likely did include meaningful goals previously. A recent metaanalysis illustrates that social priming effects are indeed stronger when relevant goals are being pursued [40,41]. Strong effects of self-relevance in the social priming literature further illustrate this point [28,29].…”
Section: Reconceptualizing Social Primingmentioning
confidence: 92%
“…If no meaningful goal exists for the person in the current situation, then the broad ensemble of situational cues is unlikely to activate relevant situated conceptualizations, which most likely did include meaningful goals previously. A recent metaanalysis illustrates that social priming effects are indeed stronger when relevant goals are being pursued [40,41]. Strong effects of self-relevance in the social priming literature further illustrate this point [28,29].…”
Section: Reconceptualizing Social Primingmentioning
confidence: 92%
“…As discussed earlier, a premise of the situated cognition perspective is that goals can be represented alongside other internal and external situational cues within a situated conceptu- confirmed that exposure to goal-related words can trigger behavior consistent with the primed goal, especially when the primed goal is strongly valued by the individual (Weingarten et al 2016). Although much of the research into goal priming focuses on health-related behaviors, research has shown that goal priming can also be used to change other, non-health related consumer behaviors, such as the selection of environmentally sustainable products (Tate, Stewart, and Daly 2014).…”
Section: Adding Situational Cues That Activate Long-term Goalsmentioning
confidence: 99%
“…Based on the priming theory, which states that the prior exposure to a stimulus affects the automatic behavioural response to a later stimulus [68,69], the following hypotheses were developed: Hypothesis 4 (H4). Consumers being exposed to a sign superficially relating to a specific food category (e.g., seafood or dairy) buy more products from that category than people not being exposed to that prime (e.g., being exposed to a control prime or other food group primes), irrespective of the textual message attached to it.…”
Section: Hypothesesmentioning
confidence: 99%